Branched alkylphosphinic and disubstituted phosphinic and phosphonic acids: effective synthesis based on α-olefin dimers and applications in lanthanide extraction and separation. Issue 39 (3rd May 2017) - Nifant'ev, I. E.; Minyaev, M. E.; Tavtorkin, A. N.; Vinogradov, A. A.; Ivchenko, P. V.
Abstract : Branched phosphinic and phosphonic acids based on α-olefin dimers demonstrated promising results in lanthanide extraction tests. Abstract : A number of mono-alkylphosphinic acids RCH2 CH2 CH(R)CH2 P(O)(H)OH8–12 were obtained via interaction of α-olefin vinylidene dimers RCH2 CH2 C(R)CH2 3–7 (R = n -butyl, 3, 8 ; isobutyl, 4, 9 ; n -octyl, 5, 10 ; isopropyl, 6, 11 ; cyclohexyl, 7, 12 ) with H3 PO2 in an isopropanol medium at 90 °C. Hydrophosphinylation of3 by8 or PhPO2 H2 at 140 °C resulted in disubstituted acids13 and14 . Alkyl-methylphosphinic acids15–19 and functionalized alkylphosphinic acids20–22 have been synthesized via interaction of silyl ethers of mono-alkylphosphinic acids8–12 with MeI, (2-chloromethyl)pyridine, acrylic acid or acrylamide. Non-catalytic hydroalumination of3 with subsequent interaction with PCl3 and oxidation with SO2 Cl2 led to the phosphonic acid anhydride, which was further used to obtain alkylphosphonic acids23 and24 . It has been found that phosphinic acids8–12 surpass di(2-ethylhexyl)phosphoric acid (extractant P 204) in non-selective Ln 3+ extractability (Ln = La, Pr, Nd, Dy and Lu). Significantly higher selectivity for heavy lanthanide extraction (Ln = Dy, Lu), compared to that of P 204, is achieved by using a minimal excess of disubstituted phosphinic acids13–24 . Acid13, which contains two branched substituents, demonstrated unique selectivity in the extraction of Lu in the presence of the other lanthanides. Dialkylphosphinic acids16–18 and alkylarylphosphinic acid14 possess a significant potential for the Pr/Nd pair separation. Taking into account the availability of8–24 and the structural variability of the initial α-olefin dimers3–7, the newly obtained compounds represent a promising group of rare-earth element extractants.